ACADEMIC OPTIMISM, STUDENTS’ ACADEMIC MOTIVATION AND EMOTIONAL COMPETENCE IN AN INCLUSIVE SCHOOL SETTING - P.U. Ekeh; C. Njoku (European Scientific Journal, ESJ, 2014)
This is a survey research designed to determine the state of academic optimism, students’ academic motivation and emotional competence in an inclusive School in Port Harcourt, Rivers State of Nigeria. Sixty-one (61) students of the Junior and Senior Secondary School sections of the school (35 regular (normal) and 26 special needs (challenged) students) constituted the population and sample of the study. The sample was purposively drawn. Four research questions and four null hypotheses guided the conduct of the research. Three instruments were utilized for data collection. They included School Academic Optimism Scale (SAOS) developed by Hoy (2005), Academic Motivation Scale (AMS) developed by Vallerand, Pelletier, Blais, Brière, Senécal, & Vallières, (1992) and Emotional Competence Scale (ECS) developed by Bharadwaj and Sharma (1995). Mean (x) and Standard Deviation (SD) were used to answer the research questions; while t-test and One-Way Analysis of Variance (ANOVA) were used to test the null hypotheses. Results got after data analysis indicated among others that the inclusive school was rated high in academic optimism; high levels of academic motivation and emotional competence were found among the students (regular and special needs alike); the difference in academic motivation and emotional competence among regular and special needs students was statistically significant; nature of challenge was a significant factor in academic motivation and emotional competence among special needs students. Based on these results, it was recommended that inclusive schooling should be encouraged by the federal and state governments in Nigeria; since it promotes academic optimism, students academic motivation and emotional competence; special needs learners require more attention, encouragement and support from the entire inclusive school community including regular students for more positive perception of the academic optimism status of the school, enhanced academic motivation and emotional competence.